2015
DOI: 10.1136/jclinpath-2015-203144
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of bladder versus colorectal adenocarcinoma: keratin 7 and GATA3 positivity in nuclear ß-catenin-negative glandular tumours defines adenocarcinoma of the bladder

Abstract: Differential diagnosis of BAC and CAC remains difficult, but positive staining for keratin 7 in nuclear ß-catenin-negative tumours argues for BAC. Additional markers like GATA3 and p63 may be added, as positivity in some cases may be helpful. However, for reliable histological diagnosis, knowledge of comprehensive clinical data is still essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 21 publications
(24 reference statements)
1
16
0
2
Order By: Relevance
“…BAC can exhibit various phenotypes: enteric/colonic, mucinous/colloid, signet-ring cell, clear cell, hepatoid, mixed and adenocarcinoma not otherwise specified (NOS; if without a specific glandular growth pattern) [5]. This phenotypical diversity turns them into diagnostically challenging tumours, since-first of all-metastatic carcinomas must be excluded [6].…”
Section: Introductionmentioning
confidence: 99%
“…BAC can exhibit various phenotypes: enteric/colonic, mucinous/colloid, signet-ring cell, clear cell, hepatoid, mixed and adenocarcinoma not otherwise specified (NOS; if without a specific glandular growth pattern) [5]. This phenotypical diversity turns them into diagnostically challenging tumours, since-first of all-metastatic carcinomas must be excluded [6].…”
Section: Introductionmentioning
confidence: 99%
“…Another diagnostic scenario that can be periodically challenging is the distinction between CRC and primary bladder adenocarcinoma, particularly as the latter can show CDX2 expression . It has been suggested that β‐catenin immunohistochemistry (nuclear decoration seen only in CRC) may help in making this distinction, but whether A33 may also aid in this distinction should be investigated next. Finally, larger cohorts of CRC from other centres should also be studied with A33, particularly to confirm the immunomarker's sensitivity, especially in biopsy material.…”
Section: Discussionmentioning
confidence: 99%
“…A number of immunomarkers have been tested in this regard, which include CK7, CK20, CDX2, villin, thrombomodulin, a-methylacyl coenzyme-A racemase, carcinoembryonic antigen (CEA), GATA3, p63, CDH17, bcatenin, and many others. [51][52][53][54][55][56] Among all tested markers, bcatenin is the only one that can be reliably used to aid in the distinction. Specifically, nuclear b-catenin expression is detected in more than 80% of CRCs but has never been seen in primary adenocarcinoma of the bladder.…”
Section: 48mentioning
confidence: 99%
“…Specifically, nuclear b-catenin expression is detected in more than 80% of CRCs but has never been seen in primary adenocarcinoma of the bladder. 51,55,56 Instead, bladder adenocarcinomas show only membranous staining. Thus, membranous b-catenin staining will not help, but nuclear staining indicates a colorectal origin.…”
Section: 48mentioning
confidence: 99%